2021
DOI: 10.1155/2021/2958584
|View full text |Cite
|
Sign up to set email alerts
|

CGRP Regulates Nucleus Pulposus Cell Apoptosis and Inflammation via the MAPK/NF‐κB Signaling Pathways during Intervertebral Disc Degeneration

Abstract: Chronic low back pain (CLBP) has been proved to be the dominating cause of disability in patients with lumbar degenerative diseases. Of the various etiological factors, intervertebral disc degeneration (IVDD) has been the dominating cause. In the past few decades, the role and changes of nerve systems, especially the peripheral sensory fibers and their neurotransmitters, in the induction and progression of IVDD have attracted growing concerns. The expression of many neuropeptides, such as SP, NPY, and CGRP, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…The underlying mechanisms were also revealed. Although a lot of signaling pathways, such as NF-κB, phosphatidylinositol-3-kinase (PI3K), MAPK, and Wnt signaling pathways, had been reported to mediate ECM metabolism or cell apoptosis after inflammation stimulation in the NPPs [38][39][40][41], we mainly focus on NF-κB and MAPK signaling pathways that were reported on PFK15 research. According to the report about the decisive role of TNF-α-induced NF-κB signaling pathway activation and subsequent p-p65 nuclear translocation in the onset and development of IVDD [42,43], we performed western blot and immunofluorescence experiments to identify whether the above conclusion exists in our research and the results corroborated the inhibiting effect of KAN on NF-κB signaling pathway activation and p-p65 nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms were also revealed. Although a lot of signaling pathways, such as NF-κB, phosphatidylinositol-3-kinase (PI3K), MAPK, and Wnt signaling pathways, had been reported to mediate ECM metabolism or cell apoptosis after inflammation stimulation in the NPPs [38][39][40][41], we mainly focus on NF-κB and MAPK signaling pathways that were reported on PFK15 research. According to the report about the decisive role of TNF-α-induced NF-κB signaling pathway activation and subsequent p-p65 nuclear translocation in the onset and development of IVDD [42,43], we performed western blot and immunofluorescence experiments to identify whether the above conclusion exists in our research and the results corroborated the inhibiting effect of KAN on NF-κB signaling pathway activation and p-p65 nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%
“…The most enriched biological process was Response to oxidative stress, cellular component was Cytoplasm, and molecular function was Identical protein binding. More importantly, we also investigated the potential signaling pathways involved in the repair process of NPCs cocultured with MSCs, and some of these signaling pathways have been proved to play important roles in the pathophysiology of IDD [38][39][40][41][42]. TNF signaling pathway and IL-17 signaling pathway both were inflammation-related pathways, which indicated that MSCs might reduce the oxidative stress, and then improve the inflammatory status of degenerative NPCs [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…TNF signaling pathway and IL-17 signaling pathway both were inflammation-related pathways, which indicated that MSCs might reduce the oxidative stress, and then improve the inflammatory status of degenerative NPCs [38,39]. MAPK signaling pathway was another vital biolog-ical pathway in the development of IDD [40][41][42] 7 Stem Cells International degenerative NPCs cocultured with MSCs. Both relaxin and oxytocin have been demonstrated to exert important protective effects in human diseases by inhibiting the cell apoptosis [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations